Strategi Marketing Kreatif Perguruan Tinggi Dalam Menarik Minat Mahasiswa Baru: Studi Kasus: Divisi Pemasaran STAI Hasan Jufri Bawean - Shobri, Muwafiqus (International Conference on Islamic Studies, 2020)
Islamic College of Religion (STAI) Hasan Jufri Bawean, Gresik Regency, which is currently the choice of higher education studies. The research objective was to analyze the creative marketing strategies carried out by the Marketing Division of STAI Hasan Jufri Bawean in attracting prospective new students and to find out whether the promotional strategies carried out by the Marketing Division team of STAI Hasan Jufri Bawean have been carried out optimally. The research method used is a qualitative research method. The data collection technique used was in-depth interviews with the Marketing Division Manager of STAI Hasan Jufri Bawean. In addition, discussions were held with 3 respondents as informants to find out about creative marketing activities that have been carried out by the Marketing Division team of STAI Hasan Jufri Bawean to attract prospective new students. The result of the research is that the creative marketing strategy carried out by the Marketing Division of STAI Hasan Jufri Bawean has been running well, successfully achieving the target, while the image of STAI Hasan Jufri Bawean is very good, because the majority of informants prefer STAI Hasan Jufri Bawean over other campuses on Bawean Island. The conclusion of this research is that using creative marketing strategies in promoting STAI Hasan Jufri Bawean is very effective, but the Marketing Division of STAI Hasan Jufri Bawean should also consider establishing good cooperation with various online media outside the campus